2018
DOI: 10.3390/educsci8020058
|View full text |Cite
|
Sign up to set email alerts
|

High School Algebra Students Busting the Myth about Mathematical Smartness: Counterstories to the Dominant Narrative “Get It Quick and Get It Right”

Abstract: This article continues to challenge the robust myth that mathematical smartness is exemplified in individuals who consistently complete mathematics problems quickly and accurately. In so doing, I present a set of counterstories from three students in one ninth-grade Algebra 1 classroom. These students described transformative experiences in their perceptions of mathematical smartness. Analysis of interviews revealed four themes about their perceptions of mathematical smartness, including: (1) consistently and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…On the other hand, other studies such as [18] show the relation between theoretical thinking and technique in a combined paper-and-pencil environment and computer algebra. The main problems in algebra learning, many of them related to students are shown in [8], are due to its abstract reasoning and generalization, called as psychologic difficulties [9], as well as others known as cognitive-type difficulties, which are related to the use of symbols and the relations between them, as it can be seen in [10]. According to teacher's point of view, some experiences related to the way they teach algebra are shown in [11].…”
mentioning
confidence: 99%
“…On the other hand, other studies such as [18] show the relation between theoretical thinking and technique in a combined paper-and-pencil environment and computer algebra. The main problems in algebra learning, many of them related to students are shown in [8], are due to its abstract reasoning and generalization, called as psychologic difficulties [9], as well as others known as cognitive-type difficulties, which are related to the use of symbols and the relations between them, as it can be seen in [10]. According to teacher's point of view, some experiences related to the way they teach algebra are shown in [11].…”
mentioning
confidence: 99%
“…A common societal misconception is that to be good at mathematics you need to perform your calculations quickly. Dunleavy (2018) found that consistently affording time and space to value multiple solution strategies enhanced students' mathematical achievement. My goal was to wait more than 3 seconds for students to respond to my questions.…”
Section: Discussionmentioning
confidence: 96%
“…This compression provides the mathematical tools to efficiently tackle more sophisticated and complicated mathematical problems. Thus, encouraging student insight and communication should be goals in the process of teaching for understanding 3.6 Norm 6: Depth is more important than speed A student's ability to recall or answer quickly poses a difficulty for teachers [25]. Does it signal that the student has a deep understanding of compressed insights and concepts or does it signal something that it has been memorized and may not signal understanding?…”
Section: Norm 5: Mathematics Is About Connections and Communicatingmentioning
confidence: 99%